2021
DOI: 10.3390/molecules26144294
|View full text |Cite
|
Sign up to set email alerts
|

Morphologically Diverse Micro- and Macrostructures Created via Solvent Evaporation-Induced Assembly of Fluorescent Spherical Particles in the Presence of Polyethylene Glycol Derivatives

Abstract: The creation of fluorescent micro- and macrostructures with the desired morphologies and sizes is of considerable importance due to their intrinsic functions and performance. However, it is still challenging to modulate the morphology of fluorescent organic materials and to obtain insight into the factors governing the morphological evolution. We present a facile bottom-up approach to constructing diverse micro- and macrostructures by connecting fluorescent spherical particles (SPs), which are generated via th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 77 publications
0
4
0
Order By: Relevance
“…For instance, compound 4 forms one-dimensional (1D) fibrous structures, regardless of the solvent polarity [ 69 ]. By contrast, compound 2 has a strong tendency to assemble into spherical objects in THF-H 2 O mixed solutions [ 70 ], whereas the substitution of sterically crowded t -Bu groups leads to the formation of hexagonal structures such as short nanorods and long sticks. Notably, after the molecular assemblies, the fluorescence efficiencies for 1 and 2 improved by approximately 2–3%.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, compound 4 forms one-dimensional (1D) fibrous structures, regardless of the solvent polarity [ 69 ]. By contrast, compound 2 has a strong tendency to assemble into spherical objects in THF-H 2 O mixed solutions [ 70 ], whereas the substitution of sterically crowded t -Bu groups leads to the formation of hexagonal structures such as short nanorods and long sticks. Notably, after the molecular assemblies, the fluorescence efficiencies for 1 and 2 improved by approximately 2–3%.…”
Section: Resultsmentioning
confidence: 99%
“…Organotrialkoxysilanes are the most important representatives of organosilicon molecules, which are the precursors of a wide range of oligomeric, polymeric structures of great practical importance, as well as interest in academic research. [1][2][3][4][5][6][7] Thus, organotrialkoxysilanes are key reagents for obtaining such valuable products and materials as polyhedral oligomeric silsesquioxanes (POSS), [8,9] hyperbranched silsesquioxanes and siloxane dendrimers, [10][11][12][13] cyclic organosilsesquioxanes, various polysiloxane oligomeric and polymeric resins and copolymers, [2,14] as well as surface modifiers. [5,[15][16][17] Currently, the traditional methods for the preparation of such alkoxysilanes are cross-coupling, hydrosilylation, transmetalation, and substitution reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Organotrialkoxysilanes are the most important representatives of organosilicon molecules, which are the precursors of a wide range of oligomeric, polymeric structures of great practical importance, as well as interest in academic research [1–7] …”
Section: Introductionmentioning
confidence: 99%
“…Fluorescent molecular assembly systems provide an exciting platform for constructing reversibly stimuli-responsive assembled nano-and microstructures whose optical, electronic, and sensing functions can be regulated by contact and non-contact stimuli such as light, chemicals, temperature, and pressure . Many studies have reported the self-assembly of π-conjugated organic chromophores into versatile fluorescent nano-and microstructured materials with such desired functions [1][2][3][4][5][6]12,14,21]. A sufficient understanding of (i) the design of small component molecules, (ii) specific and non-specific interactions of the molecules with surrounding solvents, and (iii) three-dimensional molecular arrangements is critical to elicit responses to stimuli from the self-assembled systems.…”
Section: Introductionmentioning
confidence: 99%